Factors associated with children's seasonal influenza diagnosis by their guardians: a prospective observational study in Japan - Hiroyuki Kato; Hiroshi Osawa; Fumihiko Matsuoka; Takashi Akimoto; Tadashi Kobayashi; Hiroki Maita (CSIRO Publishing, 2022)
Introduction Children's influenza diagnosis by their guardians has been reported to be highly accurate, but clinical factors that improve the reliability of a guardian's diagnosis are unclear. Aim To determine the accuracy of guardians' influenza diagnosis of their children, investigate clinical factors that improve the diagnostic accuracy, and determine the additional clinical value of the guardian's diagnosis. Methods A prospective observational study was conducted at a primary care clinic in Japan from December 2017 to April 2019. Pre-examination checklists completed by guardians accompanying children aged <12 years with clinically suspected influenza were analysed. Receiver-operating characteristic curve analysis was performed to evaluate the diagnostic accuracy at multiple cut-off points and to compare the area under the curve (AUC), using a rapid influenza diagnostic test as the reference standard. Multivariable logistic regression was performed to validate additional contribution of guardians' diagnosis. Results A total of 112 patient pairs of child (median age, 6 years) and guardian (mother, 81.2%; father, 16.1%; grandmother, 1.8%; other, 0.9%) were included in the analysis. The AUC for guardians' influenza diagnosis was higher in mothers (0.72), as well as pairs with children with a history of influenza (0.72), guardians who were aware of the influenza epidemic (0.71), and unvaccinated children (0.76), than in other guardians. After multivariate analysis, the AUC increased significantly from 0.79 to 0.85. Discussion Guardians' influenza diagnosis for their children was highly accurate. We identified factors that improve the accuracy of the guardians' diagnosis and demonstrated that the guardians' diagnosis can support physicians' diagnostic accuracy.